«THIS PAINFUL AND NOBODY NECESSARY TRUE…» - Grosevich, T. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Review of book of Ye. Baran «In a captivity stereotypes et al essays». – Ivano-Frankivs’k: Tipovit, 2009. – 256 s.